KONTROVERSI JALAN KAKI KE BAITULLAH SAMBIL LIVE STREAMING DI MEDIA SOSIAL (KAJIAN ISTITHA'AH HAJI/UMROH PERSPEKTIF HUKUM ISLAM) - Akhmad Rudi Maswanto; Firma Yudha (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The digital era has birthed a new phenomenon in religious practices: performing the Hajj or Umrah pilgrimage on foot while broadcasting the journey through live streaming on social media platforms like TikTok. This phenomenon is often accompanied by online donation solicitations from viewers, triggering public controversy and the label of